COVID-19 Pandemic: An Experience of OBGYN Residents at Kathmandu Model Hospital - Bharati, S.; Bajracharya, N.; Tiwari, K.D.; Maharjan, O.; Maharjan, S. (Kathmandu University Medical Journal, 2020)
COVID-19, a novel corona virus has affected the life of each and every individual worldwide. Nepal being the neighborhood country of china, though, we had a late case detection. But, since the month of July this virus has spread in an alarming manner in Nepal. Nepal being one of the developing countries, we lack in equipments, manpower resources and also in treatment centers. Looking into the devastating scenario of Covid 19 in China, Italy, New York, Brazil and our neighboring countries like India, Pakistan and Bangladesh is scary. We wondered how we were going to handle this pandemic if similar circumstances happened in our country too. At the same time being OBGYN residents, we all know pregnancy is very crucial and our patients have faced much difficulties to receive the maternal health services. In this manuscript, we have shared our experience regarding preparedness for COVID-19, management of positive cases and its effect in OBGYN trainee.